Application of The Sustainable Tourism Concept in Aan Tourism Village Klungkung Regency Bali - Darma Susila, I Made Gede; Suwitra Wirya, I Made; Purnama Dewi, Desak Made (Jurnal Manajemen Pelayanan Hotel, 2023)
The development of Aan Village into a tourist village has begun in 2021 where all communities are involved. The advantages possessed by this village are tourist attractions such as Aan Secret Waterfall, Sukanta Wahyu, Bukit Kembar and Petapan Park. The objectives of this study are 1) Know the development of tourism based on the 4A concept that has been done, and 2) Know the application of the concept of sustainable tourism in Aan Tourism Village. The research method used is a qualitative descriptive approach with data collection techniques such as observation, interviews and literature studies. The results of this study found that at this time the development of tourism based on the 4A concept, especially in terms of tourist attraction, is being intensified including natural, cultural and artificial attractions. In addition, improving road access and tourism facilities is being pursued by tourism village managers and village governments. The application of sustainable tourism principles can be applied well considering that this tourism village is still included in the pilot category. Not only from the environmental side but also from the economic and cultural side of the local community. The community is involved in the planning, management, and supervision stages which can provide a sense of ownership and maintain their tourist attractions. It is hoped that with the involvement of all tourism stakeholders, sustainable tourism development can be applied in Aan Tourism Village.Keywords: Tourism Development, Sustainable Tourism, Tourism Village, Aan Village